The Development of Special Interactive Teaching Computer Programs for the Training of the Specialists of Radiological, Chemical and Biological Defence Troops - K. P. Kuznetsova; S. N. Solnyshkov (Вестник войск РХБ защиты)
The development of any weapon system is carried out by the implementation of new technologies into the military equipment. The complexity and costliness of their adaptation require the increase of the intensity of personnel training with the simultaneous reduction of material and financial costs. In this connection, it is an urgent task to arrange the conditions for the mass training of military specialists by the elaboration of the training facilities system that allow the trainees to acquire proper skills of the maintenance and combat employment of the weapons and the equipment of radiological, chemical and biological (RChB) defence in an accelerated manner. In order to solve this problem, the subprogram of the development of the system of technical means of training is developed within the framework of the Interspecific complex target program «The Development of the weapon system of the Russian Federation Land forces for the period to 2025». One of the purposes of this subprogram is to reduce the period of training of formations and military units of the Land forces to the required level with the help of computer-based forms of training. The conducted research is aimed at the solution of the problem of the accelerated education of military specialists and at the improvement of the quality of adaptation of new arms and equipment of RChB defence. The purpose of our study is to develop the proposals for the improvement of the organization of combat training by the introduction of interactive teaching computer programs into the system of technical means of training in the educational centers, military units of RChB defence, as well as into the computer work-stations of the special vehicles. The research uses dialectical, informational, analytical and logical methods, a complex of pedagogical and psychological methods, as well as methods of visualization of color materials and interactive learning. We propose the concept of an interactive teaching computer program, which allows to increase the intensity of training of RChB defence troops personell.